Monocyte Migration Driven by Galectin-3 Occurs through Distinct Mechanisms Involving Selective Interactions with the Extracellular Matrix. (25th February 2013) - Danella Polli, Cláudia; Alves Toledo, Karina; Franco, Luís Henrique; Sammartino Mariano, Vânia; de Oliveira, Leandro Licursi; Soares Bernardes, Emerson; Roque-Barreira, Maria Cristina; Pereira-da-Silva, Gabriela
Abstract : Monocyte migration into tissues, an important event in inflammation, requires an intricate interplay between determinants on cell surfaces and extracellular matrix (ECM). Galectin-3 is able to modulate cell-ECM interactions and is an important mediator of inflammation. In this study, we sought to investigate whether interactions established between galectin-3 and ECM glycoproteins are involved in monocyte migration, given that the mechanisms by which monocytes move across the endothelium and through the extravascular tissue are poorly understood. Using the in vitro transwell system, we demonstrated that monocyte migration was potentiated in the presence of galectin-3 plus laminin or fibronectin, but not vitronectin, and was dependent on the carbohydrate recognition domain of the lectin. Only galectin-3-fibronectin combinations potentiated the migration of monocyte-derived macrophages. In binding assays, galectin-3 did not bind to fibronectin, whereas both the full-length and the truncated forms of the lectin, which retains carbohydrate binding ability, were able to bind to laminin. Our results show that monocytes migrate through distinct mechanisms and selective interactions with the extracellular matrix driven by galectin-3. We suggest that the lectin may bridge monocytes to laminin and may also activate these cells, resulting in the positive regulation of other adhesion molecules and cell adhesion to fibronectin.